Consumer Protection Law: The Case Study Of Grabtoko Company In Indonesian E-Commerce Transactions (Faculty of Law, Universitas Negeri Semarang, 2021)
ABSTRACTTechnology innovation is steadily increasing its capacity in helping human activities, one of which is through digital transactions. The increased use of technology, however, could potentially create legal loopholes which may violate consumer’s rights in online transactions like the recently happened GrabToko case. This journal shall discuss and provide normative approach analysis in Indonesian customer protection law, with the reference of previous articles, seeing the increasing usage of digital transactions. This journal aims to provide an explanationregarding the advantages and the disadvantages of existing regulations and what needs to be improved related to frauds in the case of GrabToko. Furthermore, it will also be discussed about the legal responsibility of the consumer dispute settlement organizations. The results of this paper shows that there are still needs of improvements since the system has its own advantages and disadvantages, especially regarding fraud and administration systems that need to be updated in corresponding law and the development in the aspect consumer protection law.Keywords: consumer protection law; consumer; rights; transaction; regulation; consumer dispute settlementINTISARIInovasi teknologi terus meningkatkan kemampuannya dalam membantu aktivitas manusia, salah satunya melalui transaksi digital. Namun, peningkatan penggunaan teknologi berpotensi menciptakan celah hukum yang berpotensi melanggar hak konsumen dalam bertransaksi online seperti kasus GrabToko yang baru-baru ini terjadi. Jurnal ini akan membahas dan memberikan analisis pendekatan normatif dalam hukum perlindungan nasabah Indonesia, dengan mengacu pada artikel sebelumnya, melihat penggunaan transaksi digital yang semakin meningkat. Jurnal ini bertujuan untuk memberikan penjelasan mengenai kelebihan dan kekurangan regulasi yang ada serta apa saja yang perlu ditingkatkan terkait fraud pada kasus GrabToko. Selanjutnya juga akan dibahas tentang tanggung jawab hukum dari organisasi penyelesaian sengketa konsumen. Hasil dari makalah ini menunjukkan bahwa masih terdapat kebutuhan perbaikan karena sistem tersebut memiliki kelebihan dan kekurangan, terutama terkait dengan sistem penipuan dan administrasi yang perlu diperbarui sesuai peraturan perundang-undangan dan perkembangan dalam aspek hukum perlindungan konsumen.Kata Kunci: hukum perlindungan konsumen; konsumen; hak; transaksi; regulasi; penyelesaian sengketa konsumen.